(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
In this article, muscle contraction is considered from a biophysical perspective as a complex process of converting chemical energy into mechanical work, carried out through the coordinated interaction of protein structures within muscle fibers. This process is of fundamental importance for understanding the mechanisms of motor activity, regulation of physiological functions, and adaptation to physical нагрузкам. The analysis of biophysical mechanisms of muscle contraction makes it possible to reveal the features of molecular interactions that determine the strength, speed, and stability of contractions in different types of muscle tissue.